PENERERAPAN METODE DEMPSTER-SHAFER DALAM PEMBANGUNAN SISTEM PAKAR DIAGNOSA PENYAKIT KULIT - Fandli Supandi; Arif Budiman; Kusrini _ (PROSIDING SNAST, 2018)
The skin is the outermost part of the human body because they have experienced many skin problem. Skin diseases are usually due to bacterial, fungal, viral, and allergic infections. But there are still many people who do not care about skin health and lazy to consulting with a dermatologist because of several factors such as economy, busyness, doctor working time, and so forth. With this the authors will build an expert system that can diagnose about skin diseases that can be accessed online through the browser. The way of data collection is done by direct interview with the dermatologist. Data obtained from experts then written in the design of the system by using the method Dempster-Shafer, php programming language and mysql database. The dempster-shafer method for calculating probabilities is based on the values ​​of an expert on the symptoms felt by the sufferer affecting the type of illness. The result of this research is a prototype application of expert diagnosis system that allows patients to diagnose symptoms that he felt through accessible websites without must to consulting with dermatologist. Results compared to the diagnosis with the expert and by the system more or less equal to the difference of about 5 - 8%.